Web-Based Decision Support System Determination of Recipients of Covid-19 Pandemic Social Assistance Using the SAW and AHP Methods - Alfian Muhharam; Agung Triayudi; Eri Mardiani (Jurnal Mantik, 2021)
During the COVID-19 pandemic, this was not only followed by an increase in the number of positive cases caused by various reactions from people who did not care about this outbreak, but also followed by an increase in poverty, early community mobility, and security insecurity . The government plans to provide special social assistance for middle to lower class people in the face of this COVID-19 pandemic. The distribution of social assistance as a realization of the social safety net program during the COVID-19 pandemic leaves a lot of homework to do. Starting from data collection, the accuracy of target recipients of aid, to the distribution. The mechanisms for distributing aid are complicated and often not well targeted due to inappropriate criteria for beneficiaries and inaccurate / inaccurate data. Until there was a protest from residents who should have received assistance but they did not get this assistance, and vice versa. This study proposes the Analytical Hierarchy Process (AHP) method for weighting the value of each criterion and the Simple Additive Weighting (SAW) method for the ranking.